If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2b + 1)(3b + -1 + 4) = 0 Reorder the terms: (1 + 2b)(3b + -1 + 4) = 0 Reorder the terms: (1 + 2b)(-1 + 4 + 3b) = 0 Combine like terms: -1 + 4 = 3 (1 + 2b)(3 + 3b) = 0 Multiply (1 + 2b) * (3 + 3b) (1(3 + 3b) + 2b * (3 + 3b)) = 0 ((3 * 1 + 3b * 1) + 2b * (3 + 3b)) = 0 ((3 + 3b) + 2b * (3 + 3b)) = 0 (3 + 3b + (3 * 2b + 3b * 2b)) = 0 (3 + 3b + (6b + 6b2)) = 0 Combine like terms: 3b + 6b = 9b (3 + 9b + 6b2) = 0 Solving 3 + 9b + 6b2 = 0 Solving for variable 'b'. Factor out the Greatest Common Factor (GCF), '3'. 3(1 + 3b + 2b2) = 0 Factor a trinomial. 3((1 + b)(1 + 2b)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(1 + b)' equal to zero and attempt to solve: Simplifying 1 + b = 0 Solving 1 + b = 0 Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + b = 0 + -1 Combine like terms: 1 + -1 = 0 0 + b = 0 + -1 b = 0 + -1 Combine like terms: 0 + -1 = -1 b = -1 Simplifying b = -1Subproblem 2
Set the factor '(1 + 2b)' equal to zero and attempt to solve: Simplifying 1 + 2b = 0 Solving 1 + 2b = 0 Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2b = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2b = 0 + -1 2b = 0 + -1 Combine like terms: 0 + -1 = -1 2b = -1 Divide each side by '2'. b = -0.5 Simplifying b = -0.5Solution
b = {-1, -0.5}
| 3n-2n+4r= | | (5x+76)+(7x+200)=180 | | 14k-1= | | 9(2x-17)=72 | | 9(2x-17)=72 | | (2-4a)(9-5a)= | | -24=-16x^2+92x+24 | | -5y-4=26 | | -2x(2)+15x-11= | | .25(x)+.30(14)=.27(x+14) | | 3x-90=12 | | 3x-10=3x+13 | | g(x)=2x^2+3x-5g(x+2) | | 0=-16x^2+92x+48 | | (5x+148)+(7x+188)=180 | | 16-7x=-3+4 | | mx^2-5x+m=0 | | B^2+18+3b=0 | | X+y(2)=240 | | r-18=4 | | -84=3x | | (a+b)(5a-3b)= | | 30=-0.5x | | 4(x-2)=3(x) | | x+4=140 | | 3(1-7y)-14y=-7 | | 2x+3ifx=9 | | 3z=1-z | | -4(-4f-10)=3(2f-4)+2 | | 5(24.2)-32=89 | | f+k=z | | 25+25+2x=180 |